Pakistan Rural Household Panel Survey (PRHPS) 2013, Round 2 - International Food Policy Research Institute; Innovative Development Strategies (International Food Policy Research Institute, 2016)
The Pakistan Rural Household Panel Survey (PRHPS) 2013, Round 2 is the second round of the PRHPS; Round 1 was conducted in 2012. This survey aims to provide a quantitative basis to identify and address urgent economic development and policy priorities in Pakistan. Many modules and questions are consistent with the prior round. PRHPS Round 2 covers 2002 of the 2090 households surveyed during Round 1 in 76 primary sampling units in the rural areas of three provinces namely: (i) Punjab; (ii) Sindh; and (iii) Khyber Pakhtunkhwa (KPK). Information on 88 households could not be collected because they refused to respond, migrated or were not available. The sample is representative of the rural areas of Punjab and Sindh provinces, and of the rural areas in 11 of the districts in KPK province. The survey collected information on a large number of topics including sources of income, nature of employment, consumption patterns, time use, assets and savings, loans and credit, education, migration, economic shocks, governance, and participation in social safety nets. Four survey instruments were developed to collect this information. These included two household questionnaires (designed to collect individual- and household-level information from a main male and a main female respondent who were interviewed separately), a community questionnaire, and a price questionnaire.